(untitled) (International Journal of Fine, Performing and Visual Arts, ISSN: 3006-6581, 2025)
This paper investigates the intersection of dance, cinema, and identity, focusing on the global reception of international dance films. Dance films, as a hybrid form of artistic expression, merge choreography with cinematic techniques to narrate stories of personal, cultural, and social identity. By examining how audiences across different cultural contexts interpret these films, the study explores the role of dance cinema in shaping and reflecting notions of ethnicity, gender, nationalism, and diaspora.